The case of children living with incarcerated mothers in Zimbabwe's Chikurubi Prison - Matsika, A.B.; Muridzo, Noel G.; Nyanguru, A.C.; Dzingirai, V. (2020)
In Zimbabwe, as elsewhere across the world, convicted nursing mothers are often incarcerated jointly with their young children. This joint incarceration is justified on the grounds that it ensures social protection of the children who are inadvertently caught up in the incarceration process. However, whether joint incarceration of this nature really facilitates the social protection of the child is a matter that has not been adequately interrogated by researchers. This paper is based on a study on this theme, which was conducted at Zimbabwe’s Chikurubi Female Prison. At the time the research was conducted, 15 of the prison inmates were nursing their babies, and all 15 of them agreed to participate in the study. The study utilised the qualitative research design. The findings of the study revealed that the physical and social environment in the prison settings constituted a major challenge in regard to the realisation of the goal of social protection of such children. The study concluded that the deleterious effects of joint incarceration of young children with their mothers far outweighed the benefits as perceived by the state and other proponents of the policy. The paper recommends a reconceptualisation of the contemporary structure of prisons and indeed a revisit of the philosophy informing the joint incarceration of young children and their mothers.